Nematode biocontrol agents: diversity and effectiveness against phytonematodes in sustainable crop protection - KHAN, MUJEEBUR RAHMAN (Indian Phytopathology, 2016)
Plant parasitic nematodes are generally soil borne in nature, and attack underground plant parts. Since, soil population of nematodes do not build-up suddenly, biocontrol approach may serve as a practically feasible, low cost, long lasting and ecofriendly method. The nematode biocontrol fauna is highly diversified, and fungi and bacteria constitute a vast group of nematode antagonists. But, only some fungi and a few bacteria have demonstrated antagonism to a level that has been exploited commercially to control nematodes in crop fields. Commercial formulations of Dactylaria candida, Arthrobotrys robusta, Purpureocillium lilacinum, Pochonia chlamydosporia, Pasteuria penetrans, Trichoderma harzianum, T. virens, Aspergillus niger, Pseudomonas fluorescens and Bacillus subtilis have been developed and are being currently used for nematode/fungus management. In view of greater effectiveness of two or more biocontrol agents in cohabitance, a consortium of microorganisms such as P. lilacinum/T. harzianum + P. fluorescens/B. subtilis may prove more suppressive to nematodes, and hence is recommended for nematode control and soil health improvement. However, there is legal biosafety restriction on the development of a formulation with two or more microorganisms. Continued research efforts in this direction shall pave a way to overcome the existing and upcoming issues to offer suitable technology(ies) for safer and effective nematode management. Further, effectiveness of biocontrol agents vary with the area and climate, hence, local efficient isolates are required to be searched regularly.